MOTIVATION MOVES: EXAMINING OLDER ADULTS’ PHYSICAL ACTIVITY AND MOTIVATION FOR EXERCISE - Sohns, E (Innov Aging, 2018)
Physical activity (PA) has been established as a negative risk factor for the development of many chronic diseases associated with aging. However, PA tends to progressively decline with age. With the growing proportion of older adults, understanding why they choose to engage in or refrain from exercise is vital in improving the population’s overall health. Thus, this study’s purpose is to examine the relationship between older adults’ regulatory motivation for exercise and subjective and objective PA. In 78 older adults (Mage = 75 years), body composition, motivation for exercise, subjective PA, and objective PA were measured. Amotivation was associated with the sedentary/moderate activity ratio (r=.57, p<.001). Identified regulation was related to activity counts/day (r=.25, p=.03), moderate minutes/day (r=.24, p=.04), and CHAMPS (r=.35, p<.01). Finally, intrinsic regulation correlated with activity counts/day (r=.31, p=.01), activity counts/minute (r=.32, p=.01), moderate minutes/day (r=.32, p=.01), and CHAMPS (r=.30, p=.01). External regulation was not significantly related to any of the PA measures. Beyond regulatory motivations, CHAMPS was associated with activity counts/day (r=.40, p<.001), activity counts/minute (r=.42, p<.001), sedentary minutes/day (r=-.24, p=.04), and moderate minutes/day (r=.43, p<.001). The results of this study indicate that among older adults identified and intrinsic regulation may serve as important motivators for PA. Additionally, subjective PA measures may be a reliable indicator of actual PA. Future studies are needed to examine the unique effects of identified and intrinsic regulation on older adults’ motivation, given their strong correlation and significant associations with PA.